English Medium Instruction as a Local Practice Language, culture and pedagogy - Han, Jinghe (SpringerBriefs in Education, 2023)
From the perspective of translanguaging and instruction theories, this Open Access book examines Chinese English Medium Instruction (EMI) lecturers' linguistic and pedagogical characteristics. This book demonstrate that 'English' in EMI is not a monolingual issue and EMI lecturers have applied their bilingual advantages to systematically and strategically advance their pedagogy practices through a translanguaging process. This book reflects upon EMI lecturers' culture-imbedded teaching and learning philosophies and explores the implications of local classroom practices, such as topic-centered instruction and teacher presentation through demonstration. This book argues that EMI teaching is not an approach that can reach universal consent across linguistic, cultural and educational systems; it is an approach that is exclusively contextualised in the lecturers' closely related cultural and educational system, and restricted by the available resources. This is an open access book.